An integrated framework of UN and AACSB principles for responsible management education. Issue 1 (14th December 2021) - Gupta, Uma G.; Cooper, Sam
Abstract : Purpose: Given the increasing relevance of Responsible Management Education (RME) to social and human welfare around the world, this paper aims to present an integrated framework that captures the essence of the principles of RME as defined by the United Nations (UN) and further set forth and embedded in the core principles of the accrediting body of business schools, namely, the American Association of Colleges and Schools of Business (AACSB). Such a framework serves as a rigorous platform for business schools and key stakeholders to integrate and implement core RME principles to deliver long-term sustainable benefits to the communities in which they operate. Design/methodology/approach: This is a conceptual paper. The authors first define key terms of RME used in the UN and AACSB guidelines to provide a universal language for business schools to communicate with their stakeholders and to monitor RME initiatives. Next, the authors identify and map RME Principles and Standards common to both organizations that business schools can apply and integrate into their educational practices to create societal impact. Finally, they categorize the 17 Sustainable Development Goals (SDGs) of the UN into four core purposes and articulate the benefits of clear and consistent messaging that aligns with the vision and mission of the institution. Findings: The integrated framework presented here makes a unique contribution to business schools that are in the early stages of RME implementation in the following ways: It simplifies the complexity and challenges of integrating the complex RME principles outlined by the UN and the spirit of the RME principles embedded in the accreditation guidelines of AACSB; the four unique themes that emerged from our research provide business schools with a clear pathway to assess their RME progress; and the framework addresses how RME can deliver exceptional value to various stakeholders of business schools. Research limitations/implications: There are many opportunities for future researchers to expand on our work particularly, in the areas of RME-driven curriculum development and experiential learning, embedding ethics within high-impact RME practices and developing rigorous metrics to define and measure societal impact. Future researchers may also wish to expand and refine the definitions of key terms and explore the role of societal interaction as an indicator of meaningful institutional engagement with the business community. Practical implications: Business educators can use this framework that maps AACBS core RME themes to the RME guidelines of the UN to assess, establish and enhance their strategies to implement and improve RME-driven business education. Originality/value: This integrated framework makes a unique contribution to business schools by simplifying the complexity and challenges of implementing RME principles outlined by the UN and that of AACSB. By integrating the principles outlined by both the accrediting body of business schools with the ideals of the U.N in a simple and elegant framework, business schools can embrace and embark on implementing one or more of the four core RME themes identified in this paper. Implementation of these principles within a core RME theme has the potential to create a strong and unique global leadership position for a business school and its graduates.